(untitled) (American Journal of Pedagogical and Educational Research, 2024)
This article poses the problem of educating youth as fully mature individuals, which today is being solved on the basis of unique modern socio-cultural technologies, creating many conditions for youth, and also reveals the role of youth in the Eastern Renaissance, in the activities of the Jadids and the renewal of society. Theoretically and methodologically, the need to always be at the head of youth, to guide and support them is analyzed and explained. Also, the greatest attention is paid to the education of the youth of our country as those who think independently, have a broad worldview, have intellectual potential, are well-mannered, cultured, know how to feel beauty, and have high aesthetic thinking.